Effects of different mixing methods towards black seed oil-alginate emulsion characteristics. - Mohd Rus, Shaiqah; Haris @ Harith, Muhammad Salahuddin; Alkhatib, Hamzeh; Mohamed Nasir, Nur 'Abidah; Abu Bakar, Mohd Rushdi; Mohmad Sabere, Awis Sukarni; Mohd Rus, Anika Zafiah; Doolaanea, Abd Almonem (Wolters Kluwer Health, 2019)
Introduction: Black seed oil (BSO) contains active ingredient, thymoquinone which is well-known for its antioxidant property. The bitter taste of BSO makes it hard for the consumers especially children and elderly to consume it daily. Therefore, BSO is encapsulated in alginate beads in micrometre size to improve its palatability. This encapsulation was already established in the lab scale. Production of the beads in a large quantity requires initial preparation of an optimised BSO-alginate emulsion starting with the different mixing methods including the sonication process. Objectives: This study aims to prepare an optimised BSO-alginate emulsion using different types of mixing instruments and flow cell of the sonication process. Materials and Methods: BSO-alginate emulsion was prepared using magnetic stirrer (MS) as the benchmark, overhead stirrer (OS), homogeniser (H) and overhead stirrer combined with homogeniser (OSH). Then, the coarse emulsion was sonicated to produce a stable emulsion. The studied parameters were mixing time, turbidity, droplet size and zeta potential. The results of each mixing method were then analysed statistically. Results: The time taken for alginate to completely dissolve in BSO emulsion for MS, OS, H and OSH were 45, 230, 102 and 46 minutes respectively. Turbidity of BSO-alginate emulsion using OSH was significantly (p<0.05) lower than the benchmark indicates a more stable emulsion. There were no significant differences (p<0.05) between the droplet size and zeta potential of OSH and MS emulsions. Conclusion: OSH gives better emulsion characteristics in terms of lower turbidity, similar mixing time, droplet size and zeta potential compared to MS.